Examining possible relationships between self-determination and burnout among junior athletes in sport - Moen, F.; Federici, R. A.; Abrahamsen, F. (International Journal of Coaching Science, 2015)
Junior athletes often work hard to become elite athletes. In their career they will meet a range of potential loads that they must overcome in order to reach their fully potential. Sometimes the total load becomes too much to cope with and burnout could be one consequence. In the present investigation 483 junior athletes from seven different schools for elite sports were invited to partake in an online survey of which 382 athletes responded (79%). We tested whether need satisfaction was a predictor for burnout utilizing structural equation modeling, and as hypothesized, basic needs were negatively related with burnout. Hence, for this investigation it seemed that environments that satisfy the need for autonomy, competence and relatedness might help elite youth athletes to avoid burnout. The results are discussed in regard of applied implications and possible future research.